Retenção de estudantes contemplados com a assistência estudantil na Universidade Federal da Paraíba (UFPB) - Aragão, Gabrielly Belmont de Brito Lima (2021)
The current research aimed to understand the factors that influence the retention of students from UFPB, Campus I, benefited with Student Assistance. Public policies for the expansion and democratization of access to post-LDB public higher education contributed to people, who were previously excluded from this level of education, to have the opportunity to be admitted to universities. However, based on Zago (2006); Ristoff (2008); Castelo Branco; Jezine; Nakamura (2015) and Bourdieu; Champagne (2012), we start from the understanding that just ensuring the access is not enough for low-income students to remain in Higher Education and reach the goal of completing their undergraduate course. The National Student Assistance Program (PNAES) is one of the strategies for students staying in Higher Education Federal Institutions (IFES), having as one of the objectives to reduce retention and dropout rates, however, according to Paula´s study (2017), even after the institutionalization of this Program, there is a drop in the undergraduate rate in public higher education. Thus, thinking about permanence with quality requires a dialectical approach, considering actions to prevent student retention that minimize dropout and, consequently, favor permanence. In this scenario, the research is exploratory and descriptive, with a qualitative-quantitative approach and of an applied nature, using bibliographic and documentary research as data collection procedures, in addition to the use of a questionnaire with students. The results pointed out that retention is multifactorial and, in our study, some factors were classified as medium/high intensity, namely: student-related factors (difficulty in learning, emotional problems, difficulty in adapting to the university, health and maternity problems); factors related to the Institution (professor, mainly regarding methodology, lack of institutional support and curriculum organization); external factor (financial difficulty). Taking this plurality of factors into consideration, the retention responsibility should not fall only on the student, it is also up to the Institution to adopt measures to minimize and/or prevent the occurrence of this phenomenon.